2021
DOI: 10.1038/s41598-021-98423-9
|View full text |Cite
|
Sign up to set email alerts
|

Non-invasive diagnostic tool for Parkinson’s disease by sebum RNA profile with machine learning

Abstract: Parkinson's disease (PD) is a progressive neurodegenerative disease presenting with motor and non-motor symptoms, including skin disorders (seborrheic dermatitis, bullous pemphigoid, and rosacea), skin pathological changes (decreased nerve endings and alpha-synuclein deposition), and metabolic changes of sebum. Recently, a transcriptome method using RNA in skin surface lipids (SSL-RNAs) which can be obtained non-invasively with an oil-blotting film was reported as a novel analytic method of sebum. Here we repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 45 publications
0
20
0
Order By: Relevance
“…This comprehensive analysis method using SSL-RNAs is expected to contribute to solving these clinical and research issues owing to advantageous features such as non-invasiveness and ease of sampling. Further, since the skin is called the disease-sensor organ and is believed to reflect the conditions inside the body 60 , 61 , the SSL-RNA analysis may have wide applicability to understand various pathologies of human body.…”
Section: Discussionmentioning
confidence: 99%
“…This comprehensive analysis method using SSL-RNAs is expected to contribute to solving these clinical and research issues owing to advantageous features such as non-invasiveness and ease of sampling. Further, since the skin is called the disease-sensor organ and is believed to reflect the conditions inside the body 60 , 61 , the SSL-RNA analysis may have wide applicability to understand various pathologies of human body.…”
Section: Discussionmentioning
confidence: 99%
“…Another research group 22 who used sensory array to detect the volatile organic compounds to identify patients with PD found sensitivity, specificity, and accuracy values of 79%, 84%, and 81%, respectively, in a small sample (29 PD, 19 control subjects). Uehara and colleagues 23 observed that by comparing sebum RNA profiles between patients with PD (23 drug naïve and 42 medicated) and controls (N = 65) they can efficiently discriminate these two groups of subjects, with similar sensitivity and specificity values, both being 69%. Our study, with double-blinding, well-matched controls, and a larger sample size, seems more robust.…”
Section: Discussionmentioning
confidence: 99%
“…The collection of SSLs and purification of SSL‐RNAs were performed according to previous reports with slight modifications 19,24 . In brief, sebum specimens were collected from whole faces of the study participants by wiping the skin surface for <1 min using a single sheet of oil‐blotting film (5.0 × 8.0 cm; 3 M Japan, Tokyo, Japan) per participant.…”
Section: Methodsmentioning
confidence: 99%
“…Data analyses were performed according to previous reports 19,24 . The normalization and statistical analysis of the AmpliSeq transcriptomic data were performed using R language.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation